Functional analysis of Pogostemon cablin farnesyl pyrophosphate synthase gene and its binding transcription factor PcWRKY44 in regulating biosynthesis of patchouli alcohol - Wang, Xiaobing; Tang, Yun; Huang, Huiling; Wu, Daidi; Chen, Xiuzhen; Li, Junren; Zheng, Hai; Zhan, Ruoting; Chen, Likai (Frontiers in Plant Science, 2022)
Farnesyl pyrophosphate synthase (FPPS) plays an important role in the synthesis of plant secondary metabolites, but its function and molecular regulation mechanism remains unclear in Pogostemon cablin. In this study, the full-length cDNA of the FPP synthase gene from P. cablin (PcFPPS) was cloned and characterized. The expressions of PcFPPS are different among different tissues (highly in P. cablin flowers). Subcellular localization analysis in protoplasts indicated that PcFPPS was located in the cytoplasm. PcFPPS functionally complemented the lethal FPPS deletion mutation in yeast CC25. Transient overexpression of PcFPPS in P. cablin leaves accelerated terpene biosynthesis, with an ~47% increase in patchouli alcohol. Heterologous overexpression of PcFPPS in tobacco plants was achieved, and it was found that the FPP enzyme activity was significantly up-regulated in transgenic tobacco by ELISA analysis. In addition, more terpenoid metabolites, including stigmasterol, phytol, and neophytadiene were detected compared with control by GC-MS analysis. Furthermore, with dual-LUC assay and yeast one-hybrid screening, we found 220 bp promoter of PcFPPS can be bound by the nuclear-localized transcription factor PcWRKY44. Overexpression of PcWRKY44 in P. cablin up-regulated the expression levels of PcFPPS and patchoulol synthase gene (PcPTS), and then promote the biosynthesis of patchouli alcohol. Taken together, these results strongly suggest the PcFPPS and its binding transcription factor PcWRKY44 play an essential role in regulating the biosynthesis of patchouli alcohol.